Variación morfosintáctica y enseñanza del español como lengua extranjera: reflexiones de un lingüista metido a profesor - Sánchez Avendaño, Carlos (2004)
In this paper a critical revision about Spanish language morphosyntactic variation treatment is carried out from the textbooks published for its teaching as a foreign language. The main purpose is to state some general cornmentaries conceming the importance of considering the heterogeneity of the language in the classroorns.